Current transport in ZnO/Si heterostructure grown by laser molecular beam epitaxy - 滕晓云 吴艳华 于威 高卫 傅广生 (Chinese physics B, 2012)
The n-ZnO/p-Si heterojunction was fabricated by depositing high quality single crystalline aluminium-doped n-type ZnO film on p-type Si using the laser molecular beam epitaxy technique. The heterojunction exhibited a good rectifying behavior. The electrical properties of the heterojunction were investigated by means of temperature dependence current density-voltage measurements. The mechanism of the current transport was proposed based on the band structure of the heterojunction. When the applied bias V is lower than 0.15 V, the current follows the Ohmic behavior. When 0.15 V ~ V 〈 0.6 V, the transport property is dominated by diffusion or recombination in the junction space charge region, while at higher voltages （V 〉 0.6 V）, the space charge limited effect becomes the main transport mechanism. The current-voltage characteristic under illumination was also investigated. The photovoltage and the short circuit current density of the heterojunction aproached 270 mV and 2.10 mA/cm^2, respectively.